Development of family‐based follow‐up care system for patients with burn in Iran: Participatory action research - Mojgan Lotfi; Vahid Zamanzadeh; Ali Ostadi; Maryam Jalili Fazel; Afsaneh Nobakht; Mohammad Khajehgoodari (Wiley, 2020)
Abstract Aim After the discharge of patients with burns, quality of life, psychological and social adjustment, performance and their follow‐up are ambiguous. Therefore, we decided to improve the status of family‐based care programmes in patients with the burn. Design Participatory action research. Methods The participatory action research was conducted between the Faculty of Nursing, Sina Hospital's managers and multidisciplinary burn teams from 2017-2018. The procedure for data collection included focus group meetings with key informants, interviews, observation, and questionnaire. Qualitative data were analysed using the qualitative content analysis and qualitative data were analysed by SPSSv.24. Results The study, comprised of four phases, started in May 2017 and completed in 9 months. The results of quantitative showed that quality of life has a statistically significant difference before and after the action. The qualitative data resulted were grouped into 3 categories and 28 subcategories and were analysed in the SWOT Matrix. All the multidisciplinary burn teams together with the managers as a team working of the care providers and the academic researcher resulted in enablers the changes in providing health education and services as well as improving the quality of life of patients and their families.